Respons Pertumbuhan dan Produktivitas Tomat Terhadap Berbagai Dosis MOL Limbah Buah-Buahan - Ari Faldi Setyana Abadi; Eny Wahyuning Purwanti; I Gede Nyoman Muditha (Jurnal Ilmu Pertanian Indonesia, 2022)
The purpose of this study was to determine the response of growth and productivity of tomato plants to the application of various doses of local microorganisms obtained from fruit waste. The study used a completely randomized design with 4 treatments and 6 replications. Observation parameters consisted of plant height (cm), number of leaves (strands), productivity (grams), and number of fruits. The best application results were at a dose of 30 ml per plant. The parameter of plant height at a dose of 30 ml produced an average of 114.83 cm, the parameter of the number of leaves produced an average of 190.83 strands, then the parameter of the number of fruits produced an average of 7.5 pieces, and the last parameter was the average fruit weight -an average of 446.16 grams. MOL affects the growth and productivity of tomato plants because it contains macro and micro nutrients and contains various microbes that are beneficial to plants. Keywords: dosage, MOL application, tomato growth, tomato productivity